2006
DOI: 10.1063/1.2188596
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Hall effect in a diffusive two-dimensional electron system with spin-orbit coupling under an in-plane magnetic field

Abstract: It is shown that a finite spin-Hall current can be induced by applying an in-plane magnetic field in a diffusive two-dimensional electron system with the Rashba and Dresselhaus spin-orbit couplings subjected to a dc electric field. The spin-Hall conductivity depends not only on the strength and direction of the magnetic field, but also strongly depends on the form of the scattering potential. It can be negative or positive in the case of remote impurity scattering, but essentially positive in the case of short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…The δ-form short-range or the remote charged impurity scattering is considered in the calculation. The scattering matrix of remote electron-impurity scattering takes the form |u(q)| effective mass at the band bottom m = 0.04m e (m e is the free electron mass); remote impurities in the InSb barrier are located at a distance of s = 10 nm from the interface of the heterojunction [22,28]. …”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The δ-form short-range or the remote charged impurity scattering is considered in the calculation. The scattering matrix of remote electron-impurity scattering takes the form |u(q)| effective mass at the band bottom m = 0.04m e (m e is the free electron mass); remote impurities in the InSb barrier are located at a distance of s = 10 nm from the interface of the heterojunction [22,28]. …”
Section: Numerical Resultsmentioning
confidence: 99%
“…CISP is found to be proportional to the SOC constant and independent of the electron density for a 2DEG with k-linear Rashba or Dresselhaus SOC when a dc electric field is applied [3,5,11]. However, situations may become different for a 2DEG with non-linear SOC, just like the spin Hall effect [15][16][17][18][19][20][21][22]; the investigation of CISP in this system is desirable. Liu et al studied CISP in a hole-doped two-dimensional system lacking structure inversion symmetry, and they found that CISP is dependent on the Fermi energy, in vivid contrast against the case in a 2DEG with k-linear SOC [23].…”
mentioning
confidence: 99%
“…This effect was also calculated in a quasi-1D system in the presence of disorder [23]. In the presence of an in-plane magnetic field, it was shown that the spin Hall conductance in a 2DEG has an anisotropic dependence on the direction of the field [24,25], while Trushim et al showed that the spin accumulation due to the extrinsic spin Hall effect has a similar dependence on the direction of electron momentum as that shown in Fig. 1a below [26].…”
mentioning
confidence: 86%
“…19 Study on the same field configuration, but in an extrinsic SOI normal metal, has found similar field suppression in another physical quantity: the out-of-plane spin-Hall potential. 20 For the intrinsic SOI, studies on the in-plane magnetic-field effects have focused on the spin-Hall conductivity 21,22 and the bulk spin densities 11,23 but not on the symmetry properties. Thus it is legitimate to perform a thorough and systematic investigation on both the spatial as well as the field-dependent symmetry characteristics of the spin distributions for the case of intrinsic SOI.…”
Section: Introductionmentioning
confidence: 99%